2018
DOI: 10.4018/ijmfmp.2018010102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters on Hole Diameter Accuracy in High Pressure Through Coolant Peck Drilling Using Taguchi Technique

Abstract: Machining with pressurized coolant is nowadays widely accepted technique in the manufacturing industry, especially in high performance machining conditions. The data on the effects of variation of high coolant pressure in drilling operation is limited. This paper presents the effect of high coolant pressures along with spindle speed, feed rate and peck depth on hole diameter accuracy. Experiments were performed on EN9 steel with TiAIN coated through coolant drill on CNC vertical machining center. Taguchi techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The lowest thrust force is measured at a high level of the speed of the spindle and coolant pressure in drilling Nimonic C-263 alloy using AlcrN coated drill. When the coolant pressure is increased, more amount of nano scaled nano fluid is entered into the cutting zone and reduce the friction in the cutting zone, thus thrust force is reduced [14]. The thrust force (559.974 N) measured at low level of spindle speed and coolant pressure is 1.10 times higher than the thrust force (509.972 N) observed at high spindle speed and coolant pressure.…”
Section: Process Parameter's Effect On Thrust Forcementioning
confidence: 86%
See 1 more Smart Citation
“…The lowest thrust force is measured at a high level of the speed of the spindle and coolant pressure in drilling Nimonic C-263 alloy using AlcrN coated drill. When the coolant pressure is increased, more amount of nano scaled nano fluid is entered into the cutting zone and reduce the friction in the cutting zone, thus thrust force is reduced [14]. The thrust force (559.974 N) measured at low level of spindle speed and coolant pressure is 1.10 times higher than the thrust force (509.972 N) observed at high spindle speed and coolant pressure.…”
Section: Process Parameter's Effect On Thrust Forcementioning
confidence: 86%
“…Higher value of thrust force is observed at low spindle speed and at low coolant pressure. This was owing to that, as the coolant pressure decrease, cooling, lubrication and chip removal abilities of coolant decrease [14]. However, the thrust force value is reduced on increasing the level of the spindle speed and coolant pressure.…”
Section: Process Parameter's Effect On Thrust Forcementioning
confidence: 99%
“…The control and constant input process parameters were selected as shown in Table 1. The levels and orthogonal array for conduction of experiments were developed using Taguchi method [16,17]. The range and levels for process parameters were chosen as shown in Table 2, based on the literature review and the practice in the welding industry.…”
Section: Experimental Designmentioning
confidence: 99%
“…Da studied polycrystalline diamond tool performance and concluded that HPC results in improved tool life of about 9 to 21 times that of conventional coolant supply. Shete and Sohani (2018) studied the effect of HPC along with spindle speed, feed rate and peck depth on hole diameter accuracy in the drilling process using Taguchi technique. The results showed that higher values of coolant pressure and spindle speed results in reduced hole diameter error in drilling.…”
Section: Introductionmentioning
confidence: 99%